Unveiling Transforming Agrifood Systems in South Asia (TAFSSA): A visual journey into context, objectives, and expected outcomes - Nur-A-Mahajabin Khan (International Maize and Wheat Improvement Center, 2023)
The video documentary is an introductory statement about TAFSSA where it says the context and objective of the initiative visually. Also, it shows its theory of change and the expected outcomes. It contains video interviews with core initiative and work package leads.